Tumpeng: Cultural, historical, and nutritional analysis of Indonesia’s traditional rice dish - Surya, Reggie; Nurfatimah, Ratna Palupi; Nugroho, David; Tedjakusuma, Felicia (jurnal1, 2025)
Tumpeng, a traditional Indonesian ceremonial dish characterized by its distinctive conical shape, accompanied by an array of side dishes. Tumpeng holds significant cultural, philosophical, and nutritional value within Indonesian society. Despite its prominence in Indonesian culinary traditions, there exists a notable gap in comprehensive literature addressing the multifaceted aspects of tumpeng. This review aims to fill this gap by providing a comprehensive examination of tumpeng, encompassing its historical evolution, philosophical underpinnings, varieties, and nutritional attributes. The historical evolution of tumpeng is rooted in ancient Hinduism in Indonesia which has evolved and adapted, reflecting the dynamic interplay between culture, religion, and tradition in Indonesian society. Philosophically, tumpeng embodies the concepts of gratitude, harmony, and community. It serves as a means of expressing gratitude to the divine and fostering communal unity through shared meals and ceremonies. Additionally, tumpeng holds symbolic significance in various cultural rituals and celebrations, reflecting the interconnectedness between spirituality, tradition, and everyday life. The review also explores the 15 varieties of tumpeng, ranging from traditional ceremonial dishes to modern adaptations for special occasions. Each variation of tumpeng carries its own unique cultural significance and culinary characteristics, highlighting the diversity of Indonesian cuisine and culinary traditions. Furthermore, a nutritional analysis reveals the potential health benefits of tumpeng, with its balanced combination of staple foods, proteins, vegetables, and other nutritious ingredients. Tumpeng offers a rich source of essential nutrients, contributing to overall health and well-being when consumed as part of a balanced diet.